Synthesis of carbon nanomaterials from carbon dioxide using pre- and post-combustion fly ash as a catalyst - Dlamini, Ndumiso (My University, 2022)
Carbon nanomaterials (CNMs) such as carbon nanotubes (CNTs) and carbon nanofibers (CNFs) have become the most prominent fields of study in nanotechnology. This is due to their fascinating and unique features such as their chemical, mechanical, electrical, and optical properties. These characteristics have paved a way for applications in fields of medicine, electronics, and polymers, among others. For their applications, highly reliable synthesis methods that can produce CNMs of high purity in large quantities are desired with less cost. Their synthesis generally requires a catalyst, carbon source, and heat. The carbon sources and catalysts used are toxic and expensive. Furthermore, the catalysts must be prepared which is time-consuming and incurs more costs. This has acted as a major motivating factor to find and compare alternative reagents that are available in abundance, cheap, non-toxic, and can be used as received with no pre-treatments. Such materials, fly ash and carbon dioxide, were used in this investigation to develop a synthesis method for the production of CNMs. Pre-combustion (Sasol) and post-combustion (Eskom) fly ash are characterized and compared based on their catalytic ability to produce pure, good crystalline CNMs in high yields. Carbon dioxide (CO2) and acetylene were used as carbon sources. Chemical vapour deposition (CVD) is used for their synthesis which allows the tuning of certain parameters. The growth of CNMs is influenced by several process parameters such as catalyst mass, temperature, and flow rates of the carbon source gas, and carrier gas. The fly ash catalysts and CNMs were characterized using FESEM coupled with EDS, XRD, XRF, particle size, and Zeta Potential Analyzer, TEM, and TGA. SEM analysis revealed that Sasol fly ash (S-FA) contains a significant number of spheres that are poorly rounded, containing coarser, chipped, and uneven surfaces. While the SEM analysis of Eskom fly ash (E-FA) showed finer and well-rounded spheres. The particle size distribution (PSD) was similar (2.8-88 μm) in both catalysts. However, the proportion of small and large particles were higher in S-FA. Furthermore, S-FA contained significant amounts of irregular fragments and E-FA contained more spherical particles. The sizes and shapes of catalysts influenced the morphology and structure of CNMs. XRF analysis showed a higher Loss on Ignition (LOI) and Fe content in S-FA (LOI=8.5 wt% and Fe=4.51 wt%) than E-FA (LOI=0.9 wt% and Fe=3.33 wt%). It was found by EDS that high Fe content is mostly concentrated on the irregularly shaped fragments than the sphere particles in S-FA. Whereas E-FA spheres showed higher Fe content. Using CO2 as a carbon source, S-FA had better yields, purity, and crystallinity than E-FA. SEM analysis of E-FA showed crystallization of the minerals present in it with no identifiable CNMs. Raman spectroscopy of E-FA did show nanomaterials containing poor graphitization. TGA showed that synthesized CNMs had a high level of impurities. Optimum yields and crystallinity for S-FA catalyst were obtained at 750 ℃, a CO2 flow rate of 962 sccm and argon (Ar) flow rate of 1202 sccm, and a mass catalyst of 1000 mg. The morphologies of CNMs found on the spheres were different from morphologies of CNMs on the irregular fragments. The pressure was found to be more influential on the yield and quality of the carbonaceous products than the flow rate. When C2H2 was the carbon source, the results were consistent with CO2. CNFs in good yield and good quality were formed in S-FA than in E-FA. CNFs with uniform large diameters were formed in S-FA from the large catalyst size. For E-FA, TEM analysis and DTG revealed growth of CNFs, CNTs, and carbon microspheres (CMS). These results show that CO2 and fly ash can be converted to commodity products, which can contribute towards mitigating their negative impact on the environment and generate monetary value from them. Sasol fly ash was also found to be superior to Eskom fly ash for the production of CNMs under all conditions.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and Built Environment, University of Witwatersrand, Johannesburg, 2021